Ultrasound-assisted extraction of Peucedanum ostruthium leaves: a feasible alternative to rhizomes for industrial applications - Chen, Chih-Yu; Wang, Guey-Horng; Kuo, Jong-Tar; Lin, Yueh-Te; Huang, Hsiu-Ju; Chang, Yu-Chi; Chung, Ying-Chien (Frontiers in Pharmacology, 2025)
This study investigated the feasibility of using Peucedanum ostruthium leaves, typically regarded as waste, as a substitute for the widely used rhizome. To identify the optimal parameters for ultrasound-assisted extraction of P. ostruthium leaves, we used Box–Behnken design in combination with response surface methodology. The optimal parameters were as follows: ethanol, 80%; extraction temperature, 61.0°C; ultrasonication duration, 35.5 min; liquid-to-solid ratio, 20; and ultrasonic power, 249 W. The half-maximal inhibitory concentration for the inhibition of extracellular tyrosinase activity, scavenging of free radicals, and suppression of various aging-related and inflammatory enzymes by P. ostruthium leaf extract (POLE) were 62.30, 20.62, 8.63, 40.82–91.23, and 12.8–126.4 mg/L, respectively. The minimum bactericidal concentration and minimum fungicidal concentration of POLE for the microorganisms tested in this study were 150–350 and 400–500 mg/L, respectively. Therefore, POLE exhibited strong whitening, antiaging, anti-inflammatory, and antimicrobial properties, surpassing those of the rhizome extract. Furthermore, POLE was biologically safe at concentrations of ≤500 mg/L. The extract exhibited remarkable wound healing capacity (92.5%) at 25 mg/L. The average efficiency of transdermal absorption and penetration reached 98%. A total of 34 predominant volatile organic compounds and 19 major nonvolatile organic compounds were identified in POLE. Molecular docking analysis attributed POLE’s whitening effects to both phenolic acids and flavonoids and its antiaging effects to mainly flavonoids. Furthermore, POLE’s anti-inflammatory and antimicrobial effects were attributed to flavonoids and coumarins. Overall, as a viable alternative to imported P. ostruthium rhizome extract, POLE holds promise for applications in cosmeceutical, healthcare, and medical products.